ACE2 and TMPRSS2 expression in patients before, during, and after SARS-CoV-2 infection - Grisard, Henrique Borges da Silva; Schörner, Marcos André; Barazzetti, Fernando Hartmann; Wachter, Julia Kinetz; Valmorbida, Manoela; Wagner, Glauber; Fongaro, Gislaine; Bazzo, Maria Luiza (Frontiers in Cellular and Infection Microbiology, 2024)
During the SARS-CoV-2 pandemic angiotensin-converting enzyme 2 (ACE2) and transmembrane serine protease 2 (TMPRSS2) were constantly under the scientific spotlight, but most studies evaluated ACE2 and TMPRSS2 expression levels in patients infected by SARS-CoV-2. Thus, this study aimed to evaluate the expression levels of both proteins before, during, and after-infection. For that, nasopharyngeal samples from 26 patients were used to measure ACE2/TMPRSS2 ex-pression via qPCR. Symptomatic patients presented lower ACE2 expression levels before and after the infection than those in asymptomatic patients; however, these levels increased during SARS-CoV-2 infection. In addition, symptomatic patients presented higher expression levels of TMPRSS2 preinfection, which decreased in the following periods. In summary, ACE2 and TMPRSS2 expression levels are potential risk factors for the development of symptomatic COVID-19, and the presence of SARS-CoV-2 potentially modulates those levels.